Whistle-blowing by external auditors in South Africa. Issue 5 (2nd June 2014) - Maroun, Warren; Atkins, Jill
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore how notions of disciplinary power manifest themselves in audit regulatory developments. When it comes to research on the relationship between audit quality and regulation, much of the prior scholarly work has kept to the positivist tradition of quantitative analysis under the guise of "economic rationality". In contrast, this research takes an interpretive approach to provide an alternate and unique perspective, using motifs of Foucauldian power and control to illuminate the operation of external regulation in a South African setting. The paper examines what may be loosely described as a mandatory whistle-blowing duty imposed on external auditors. Design/methodology/approach – Detailed interviews with some of South Africa's leading corporate governance experts are used to highlight the disciplinary effect of an auditor's duty to bring reportable irregularities to the attention of an independent regulator. Findings – Blowing the whistle on irregularities contributes, not only to increasing the information made available to stakeholders, but to creating a valid expectation of auditors serving the public interest by enhancing a sense of transparency and accountability. Elements of resistance to panoptic-like control are, however, also present suggesting that, in part, the regulation may simply be creating the illusion of active reporting. Research limitations/implications – The research relies on a relatively small sample of subject experts and does not provide a complete account of regulatory developments taking place in South Africa and abroad. Additional research on the role of whistle-blowing in an external audit setting is needed focusing particularly on similarities and variations in interpretations of reporting by auditors from the perspective of more diverse stakeholder groups. Practical/implications – Mandatory reporting of irregularities by auditors can provided additional useful information for stakeholders and may contribute to demands for more effective reporting by auditors. Social implications – Arms-length regulation of the audit profession should not be seen only as a means of improving audit quality and the utility of audit reports. Powerful social forces are also. This research demonstrates how laws and regulations have a potential disciplinary effect on the audit profession that contributes to a restoration of confidence in the audit process after it is best by scandals, even if motifs of power and control are somewhat illusionary. Originality/value – This research addresses the need for more detailed analysis of precisely how mechanisms of accountability and transparency operate in the broader corporate governance arena. The paper also contributes to the calls for more detailed, context-specific studies of audit. Finally, this paper is one of the first to employ a critical theoretical perspective on audit in an African setting, responding to the need for contextual, methodological and theoretical eclecticism in the area of corporate governance research.